Parametric investigation of agent-based modeling in algorithmic development of curved surfaces. (March 2023) - Umashankar, Bhoomika
Architects aspire to build iconic buildings and focus on experimenting with non-standard forms. The construction of non-standard forms is challenging. This has led many researchers and facade designers to develop and resolve the complexity of forms to simpler, buildable elements. In this progress, the tessellation of non-standard surfaces has experimented considerably with different approaches using computational tools. All the approaches from researchers or facade engineers have limited access for every designer. As they develop patented software or use any coding languages which are not accessed by any open-source platform. Hence in academia, it is difficult to experiment in this domain. This paper analyzes the existing panalization computational tools and different approaches used by researchers worldwide in developing complex curved surfaces. Analyzing the relevant cases led to identifying the gap in current research. This has led to investigate and explore a new algorithmic process using an existing computational tool: Agent-based modeling on an open-source tool (Grasshopper-Visual programming language), which is phase -1 of the Master's thesis.